An evaluation of the community-based participatory extension approach (pea) in okehi local government area, of kogi, state nigeria - Onipe, Saliu Hassan; Michael, Odoma; Hassan, Emeje; Kolawole, Olajide (Journal of Management and Science, 2013)
This study was carried out to evaluate the community-based participatory extension approach in Okehi Local Government Area of Kogi State. The specific objectives were to examine the socio-economic profile of the farmers, level of participation, effectiveness of the PEA model in addressing farmers technological needs and problems militating against effective operation. Data were collected using structured interview schedule from 60 respondents who were randomly selected. The data collected were analyzed by the use of descriptive statistics such as tables, percentages frequencies and means. The Result from the analysis showed that 60 percent were within (40-59years) which could be considered to be the age bracket for economically active population. The level of participation was found to be (65 percent). The study shows that the community-based participatory extension approach has positive effects in the area because production was higher after the intervention of PEA model. The major problem identified with the PEA model in the area include, illiteracy, inputs not readily available, approach is time consuming, lack of credit as well as inadequate extension contact. The study concluded by recommending that efforts should be intensified on provision of adequate rural infrastructure like school, feeder roads and marketing outlet for the farmers produce. This would help improve and sustain the gains accruable from participating in this project.